Is it possible to predict the development of osteopenia in patients with juvenile idiopathic arthritis? - T.V. Marushko; Yu.Ye. Holubovska (Zaslavsky O.Yu., 2019)
Background. A musculoskeletal disorder is a key manifestation of juvenile idiopathic arthritis (JIA). One of the disease complications is the development of osteopenia. An important addition to determining the bone mineral density (BMD) is the evaluation of biochemical markers such as osteocalcin and 25-hydroxyvitamin D (25(OH)D). Our purpose was to evaluate the densitometry data, the levels of serum osteocalcin and 25-hydroxyvitamin D in JIA patients, depending on the received treatment, in order to determine the indicators of bone metabolism disorders, so that the development of osteopenic syndrome could be prevented, or the treatment should be initiated. Materials and methods. BMD, the levels of osteocalcin and 25(OH)D in the blood serum were evaluated in 134 JIA patients. The calculations were processed using Pearson's Chi-square test, Student's t-test, and Spearman's rank correlation coefficient. Results. Secondary osteopenic syndrome was detected in 38 % of JIA patients, and the vitamin D deficiency - in 68 %. Patients, who received biologic disease-modifying antirheumatic drugs in their regimen of treatment, had significantly higher BMD and osteocalcin levels (p < 0.001). There is a moderate negative correlation between osteocalcin level and the inflammatory activity index according to the Juvenile Arthritis Disease Activity Score for 27 joints that indicates the presence of association between the processes of inflammatory activity development and bone remodeling. Considering the serum osteocalcin levels within 19.4-36.9 ng/ml with a sensitivity of 86 % and a specificity of 87.8 %, BMD could be determined that corresponds to the chronological age according to the results of dual-energy X-ray absorptiometry. Conclusions. It should be necessary to check the BMD status, the blood serum osteocalcin and 25(OH)D levels while observing a JIA patient to establish the algorithm of timely treatment correction.